2012
DOI: 10.1167/12.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Slow updating of the achromatic point after a change in illumination

Abstract: For a color constant observer, the color appearance of a surface is independent of the spectral composition of the light illuminating it. We ask how rapidly color appearance judgments are updated following a change in illumination. We obtained repeated binary color classifications for a set of stimuli defined by their reflectance functions and rendered under either sunlight or skylight. We used these classifications to derive boundaries in color space that identify the observer's achromatic point. In steady-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…To return to the question of what it is that underlies perception of white, it is clear from our results and those of many others (Helson & Michels, 1948;Honjyo & Nonaka, 1970;Hurvich & Jameson, 1951;Jameson & Hurvich, 1951a, 1951bLee, Dawson, & Smithson, 2012;McDermott & Webster, 2012;Webster & Leonard, 2008;Werner & Schefrin, 1993;Werner & Walraven, 1982) that white is not a single chromaticity. Different observers and even the same observer on different occasions can perceive a surprisingly large range of chromaticities as white, with this range about 2.5 times greater in the blueyellow direction than in the red-green direction.…”
Section: What Is White?mentioning
confidence: 57%
“…To return to the question of what it is that underlies perception of white, it is clear from our results and those of many others (Helson & Michels, 1948;Honjyo & Nonaka, 1970;Hurvich & Jameson, 1951;Jameson & Hurvich, 1951a, 1951bLee, Dawson, & Smithson, 2012;McDermott & Webster, 2012;Webster & Leonard, 2008;Werner & Schefrin, 1993;Werner & Walraven, 1982) that white is not a single chromaticity. Different observers and even the same observer on different occasions can perceive a surprisingly large range of chromaticities as white, with this range about 2.5 times greater in the blueyellow direction than in the red-green direction.…”
Section: What Is White?mentioning
confidence: 57%
“…The idea that the chromatic system is at a ''resting state'' at the achromatic locus has led to the use of the achromatic point as a means to scale the cone fundamentals (Bompas, Powell, & Sumner, 2013;Walraven & Werner, 1991). Experimentally, settings of the achromatic loci are widely used to establish the effect of illumination or to assess spatial or temporal context effects (see, e.g., Doerschner, Boyaci, & Maloney, 2004;Lee, Dawson, & Smithson, 2012). The extent of invariance of these achromatic settings depends on the spatial configuration, the chromaticity Citation: Chauhan, T., Perales, E., Xiao, K., Hird, E., Karatzas, D., & Wuerger, S. (2014).…”
Section: Introductionmentioning
confidence: 99%
“…Ten additional stimuli, randomly chosen from those in the session, were presented at the start of the session. In a previous study, we showed that, after a change in illumination conditions, color classification reaches steady-state levels within approximately ten 2 s trials [27]. The responses to these ten additional presentations were discarded.…”
Section: Methodsmentioning
confidence: 99%
“…If the time constants of temporal adaptation were sufficiently long, spatially localized mechanisms might be made to extract a spatial average if eye movements sampled sufficient spatial locations [26]. Indeed, we have shown that, with limited eye movements, the temporal sequence of chromaticities is equally as effective in determining color appearance as the spatial array of chromaticities [27,28]. To first approximation, temporal adaptation is set by the mean chromaticity of the sequence of chromatic samples to which the observer is exposed, at least over a time course of tens of seconds [12].…”
Section: Introductionmentioning
confidence: 99%